Dorothy West's Paradise : a Biography of Class and Color. - Sherrard-Johnson, Cherene (Rutgers University Press, 2012)
Dorothy West's Paradise captures the scope of the author's long life and career, reading it alongside the unique cultural geography of Oak Bluffs and its history as an elite African American enclave - a place that West envisioned both as a separatist refuge and as a space for interracial contact. An essential book for both fans of West's fiction and students of race, class, and American women's lives, Dorothy West's Paradise offers an intimate biography of an important author and a privileged glimpse into the society that shaped her work.